2011
DOI: 10.1001/archdermatol.2010.246
|View full text |Cite
|
Sign up to set email alerts
|

Skin Conditions That Bring Patients to Emergency Departments

Abstract: his prednisone dose. There were no serious adverse events or laboratory abnormalities. Comment. Previous case reports (6 total patients in 3 reports 1-3) describe uniformly effective results for the use of etanercept in PV. Our randomized, controlled study suggests that the response to etanercept is heterogeneous, although the small sample size precludes definitive conclusions. We observed 2 meaningful responses in the 4 patients who received etanercept and completed the study, although the use of azathioprine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 4 publications
9
53
1
1
Order By: Relevance
“…Cellulitis was the most common condition (36.1%), consistent with previous studies [7, 10]. However, the prevalence of cellulitis may be misleading, as multiple studies have reported high rates of misdiagnosis of cellulitis in ED due the lack of familiarity with more specific dermatological diagnoses such as lipodermatosclerosis and contact dermatitis.…”
Section: Discussionsupporting
confidence: 85%
“…Cellulitis was the most common condition (36.1%), consistent with previous studies [7, 10]. However, the prevalence of cellulitis may be misleading, as multiple studies have reported high rates of misdiagnosis of cellulitis in ED due the lack of familiarity with more specific dermatological diagnoses such as lipodermatosclerosis and contact dermatitis.…”
Section: Discussionsupporting
confidence: 85%
“…One reason for the low prevalence of LTD or infections in or study is that most patients with LTD or infections have systemic symptoms that make them go to the ED instead of the DD [8,13]. As a consequence, several dermatology patients are admitted and treated in non-dermatology departments without any information to the DD.…”
Section: Discussionmentioning
confidence: 99%
“…The exact frequency of dermatologic diseases and characteristics of patients have been studied in limited settings; moreover most published data are heterogeneous [1,2,3,4,5,6,7,8,9]. Reasons for heterogeneity are dissimilarities in studied parameters, such as short-/long-time studies, different referral pattern, in-hospital setting [10], ambulant setting [5,11], urgent setting [1,2,4,5,6,7,8,12,13], non-urgent setting, mixed situations, or children only [14,15,16,17]. In addition, most studies were retrospective.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] The aim was to quantify and characterize cases to provide basic information for physicians and the national health system with a view to improving patient care and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%